A new Cleotomiris species (Hemiptera: Heteroptera: Miridae: Phylinae) from North Korea - Konstantinov, Fedor; Simov, Nikolay (Zootaxa, 2014)
Cleotomiris josifovi is described from the vicinity of Pyong Kang, North Korea. The description of this new species is provided with scanning micrographs of selected structures, and digital microscopic images of habitus and genitalia.